Acianthera hagsateri (Pleurothallidinae), a new species from the sub-andean forest of Colombia - Pérez-Escobar, Oscar Alejandro; Oses, Lizbeth M.; Solano, Rodolfo; Rodríguez, Lizeth Katherine; Zuluaga, Alejandro; Bogarín, Diego (Lankesteriana: International Journal on Orchidology, 2022)
A new species of Acianthera from the relict cloud forests of Valle del Cauca, Colombia is described and illustrated. This new species, Acianthera hagsateri, morphologically resembles A. geminicaulina, A. decurrens, and A. erythrogramma, but differs from them by its shorter plants and stems, the elliptic and obtuse smaller leaves, the racemose, 1–3 flowered raceme, and the obovate, entire lip, with a pair of smooth calli reaching the apical half. Illustration, distribution map, eponymy, notes on ecology, pictures for this new species are included, and a comparison table with morphologically similar species.